Implementing an environmental management system from the bottom-up - Hietanen, Roosa Maaria (2024)
Micro-CSR has gained increasingly attention within the CSR research lately. The microfoundations of organizations have been studied to understand their impact on the company’s CSR. However, studies from the perspectives of individuals are still somewhat lacking. The purpose of this study is to give its contribution especially to the employee perspective in the micro-CSR research. This study aims to answer two research questions: 1. Which factors do employees perceive as supportive and inhibiting for the bottom-up implementation of an EMS like ISO 14001? 2. From the employee perspective how could an EMS like ISO 14001 be implemented from the bottom-up? The questions are approached by conducting 13 semi-structured employee interviews in a chosen case company. From the employee interviews there are five factors identified that employees perceive as supportive for the bottom-up implementation of an EMS. These factors are simple and practical processes; pro-environmental attitudes and values, and emotions such as guilt and anxiety; organizational culture and the supporting structures for pro-environmental behaviour within it; awareness and communication; and rewarding and other incentives. The three inhibiting factors for bottom-up implementation of an EMS that are recognized from the employee interviews are lack of time or resources; emotions of indifference, ignorance and powerlessness and lack of environmental prioritization; and regulatory and safety requirements. The actual implementation of an EMS from the bottom-up can be supported especially by engaging, empowering, and enabling the employees’ environmental action and by keeping them informed about the environmental policies and actions of the company.